Relationship between magnification and resolution in digital pathology systems - Tiffany L Sellaro; Robert Filkins; Chelsea Hoffman; Jeffrey L Fine; Jon Ho; Anil V Parwani; Liron Pantanowitz; Michael Montalto (Elsevier, 2013)
Many pathology laboratories are implementing digital pathology systems. The image resolution and scanning (digitization) magnification can vary greatly between these digital pathology systems. In addition, when digital images are compared with viewing images using a microscope, the cellular features can vary in size. This article highlights differences in magnification and resolution between the conventional microscopes and the digital pathology systems. As more pathologists adopt digital pathology, it is important that they understand these differences and how they ultimately translate into what the pathologist can see and how this may impact their overall viewing experience.